A thermo-visco-plastic damage model and SPH simulations of plugging failure. Issue 15 (10th December 2018) - Rahaman, Md Masiur; Pathak, Abhishek; Roy, Debasish
ABSTRACT: A thermo-visco-plasticity model, recently developed based on a microinertia driven dynamic flow rule, is exploited to account for damage due to fracture. This is accomplished by adjoining the equations for thermo-visco-plasticity, herein discretized through the smooth particle hydrodynamics (SPH), with a "pseudospring" based discrete damage model. In treating ductile fractures, this coupled material model accounts for the inertia associated with moving microstructural defects and time lags for the dissipative fluxes to attain the steady state. In this approach, while the microinertia-driven flow rule provides a vehicle to evolve plastic strain, pseudosprings are exploited to treat material damage and the resulting reduced force transfer. The current scheme does not necessitate the introduction of a yield or damage surface in evolving the plastic-strain/damage parameters, and thus the numerical implementation avoids a computationally intensive return mapping. We demonstrate the performance of the proposed model through SPH-based numerical simulations and also undertake a validation exercise against experimental observations from gas-gun penetration tests on an 8-mm thick Weldox 460 E steel plate.